KOMUNIKASI INTERPERSONAL VIDEOGRAPHER DAN EDITOR DALAM PEMBUATAN VIDEO WEDDING DI PASTEL WEDDING GEMOLONG SRAGEN - Musairi, Wendi; Suryo, Herning; Aji, Haryo Kusumo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
ABSTRACT Interpersonal communication between videographer and editor is important in making wedding videos. Good cooperation between videographer and editor can produce an interesting and quality wedding video. The purpose of this research is to understand how interpersonal communication between videographers and editors in the wedding video production process. This type of research is descriptive qualitative. The technique of determining informants used purposive sampling with informants Videographer and Editor. Data collection used observation and interviews. Data analysis techniques using qualitative analysis. Interpersonal communication between videographers and editors is well established where there is an atmosphere of openness, mutual attention, trust and provision of positive and constructive feedback, being friends to interact and listen to each other, and contributing equally in the video making process so that both parties work together efficiently and effectively in producing creative wedding videos. Keywords: interpersonal communication, videographer, editor, wedding video